A LuxR‐type repressor of Burkholderia cenocepacia inhibits transcription via antiactivation and is inactivated by its cognate acylhomoserine lactone. Issue 1 (19th November 2012) - Ryan, Gina T.; Wei, Yuping; Winans, Stephen C.
Summary Burkholderia cenocepacia is an opportunistic human pathogen that encodes two LuxI‐type acylhomoserine lactone (AHL) synthases and three LuxR‐type AHL receptors. Of these, cepI and cepR form a cognate synthase/receptor pair, as do cciI and cciR, while cepR2 lacks a genetically linked AHL synthase gene. Another group showed that a cepR2 mutant overexpressed a cluster of linked genes that appear to direct the production of a secondary metabolite. We found that these same genes were upregulated by octanoylhomoserine lactone (OHL), which is synthesized by CepI. These data suggest that several cepR2‐linked promoters are repressed by CepR2 and that CepR2 is antagonized by OHL. Fusions of two divergent promoters to lacZ were used to confirm these hypotheses, and promoter resections and DNase I footprinting assays revealed a single CepR2 binding site between the two promoters. This binding site lies well upstream of both promoters, suggesting an unusual mode of repression. Adjacent to the cepR2 gene is a gene that we designate cepS, which encodes an AraC‐type transcription factor. CepS is essential for expression of both promoters, regardless of the CepR2 status or OHL concentration. CepS therefore acts downstream of CepR2, and CepR2 appears to function as a CepS antiactivator.